Antropofagia no sítio : insólito ficcional e identidade cultural em Peter Pan, de Monteiro Lobato - Zobaran, Felipe Teixeira (My University, 2016)
This thesis aims at examining to what extend Brazilian writer Monteiro Lobato brings out his children's literature project in the books of the Sítio do Picapau Amarelo series, focusing especially on the novel Peter Pan, released in 1930. The original story by Scottish playwright James Matthew Barrie first appeared in a play in London in 1910, and became a contemporary classic, widely adapted and translated, including film versions by Walt Disney studios. Lobato, who was a famous translator, chose not only to translate the work of Barrie, but to absorb it into his own fiction; in the Brazilian books, the story of the boy who does not grow up is told by the character Dona Benta to her grandchildren; from there on, several fictional properties of the original British story manifest in many instances to the children of São Paulo. This feature is in line with Brazilian modernism writers of 1922, who defended Antropofagia (literary cannibalism), that is, a sharp reinforcement of the Brazilian identity in literature, by absorbing foreign aesthetics and transforming them into something original. Although Lobato was a dissident of that group, and even though his prose for adults was not very modernistic, his books for children are similar, in some ways, to what Oswald de Andrade and Mario de Andrade were producing in the early 1920’s. Based on Lajolo and Ceccantini (2008), Zilberman (1982), Vieira (2008) and White (2011), this paper shows the intertwining fiction of Barrie and Lobato, and how the Brazilian books get to defend a sort of nationalism. In Lobato’s Peter Pan, two supernatural worlds converge: Sítio do Picapau Amarelo and Neverland; thus, this paper analyses both fictional worlds based on fantasy literature theories, such as the works of Todorov (2007), Roas (2014) and García et al. (2007). Moreover, this analysis seeks to define Lobato’s view of Brazilian identity, based on Hall (2005), Said (2011) and theories of nationalism. The conclusion is that Lobato was a cultural translator, who could bring to the country's readers old and new stories that were produced abroad, making them very Brazilian, by digesting them in a cannibalistic way. His fictional influence is, actually, visible until today, as it helped in the formation of a modern Brazilian identity.
Este trabalho busca analisar como Monteiro Lobato concretiza seu projeto de construção de uma literatura infantil brasileira, em obras constituintes da coleção do Sítio do Picapau Amarelo, especialmente através do livro Peter Pan, de 1930. A personagem homônima original do escocês James Matthew Barrie apareceu pela primeira vez em uma peça de teatro em 1910, em Londres, e tornou-se um clássico contemporâneo, largamente adaptado e traduzido, inclusive pelos estúdios de animação de Walt Disney. Lobato, que era tradutor, escolheu não apenas traduzir a obra de Barrie, mas apropriar-se dela no universo do Sítio; nos livros do brasileiro, a história do menino que não quer crescer é contada pela personagem Dona Benta a seus netos; a partir daí, diversas propriedades ficcionais do original britânico se manifestam em muitos momentos na obra infantil do paulista. Esse recurso é consoante com uma prática defendida pela geração de escritores do modernismo brasileiro de 1922: a antropofagia. Embora Lobato fosse dissidente do grupo, e apesar de sua prosa para adultos ter sido pouco modernista, sua literatura infantil se mostra extremamente similar àquilo que o grupo de Oswald de Andrade e Mário de Andrade defendia. Com base em Lajolo e Ceccantini (2008), Zilberman (1982), Vieira (2008) e White (2011), este trabalho busca mostrar como se dá o entrecruzamento antropofágico da obra de Barrie com a de Lobato, e como o paulista construiu sua literatura nacionalista para crianças. Em Peter Pan de Lobato, há dois universos mágicos e sobrenaturais que se sobrepõem: o Sítio e a Terra do Nunca; o escopo analítico deste trabalho passa, então, por teóricos do modo literário insólito / fantástico, como Todorov (2007), Roas (2014), García et al. (2007), e outros. Além disso, busca-se analisar a visão do Brasil que o escritor paulista conseguia vincular à sua literatura infantil, pensando em identidade regional, nacional e no contexto de globalização, com base em Hall (2005), Said (2011), e em considerações sobre região e nação. A conclusão é que Lobato era um tradutor cultural que conseguia trazer aos leitores do país, pioneiramente, histórias antigas e novas que eram produzidas no exterior, vestindo-as à brasileira, digerindo-as de maneira antropofágica, e que sua influência ficcional é visível até os dias de hoje, no que diz respeito à formação de uma identidade brasileira moderna.
Keywords: Lobato, Monteiro, 1882-1948 - Crítica e interpretação; Peter Pan (Obra literária); Antropofagia na literatura; Literatura fantástica; Características nacionais; Lobato, Monteiro, 1882-1948 - Criticism and interpretation; Peter Pan (Literary work); Cannibalism in literature; Fantasy literature; National characteristics